KEY CONCEPTS AND PRINCIPLES OF THE ANTHROPOCENTRIC PARADIGM IN LINGUISTICS (INTERNATIONAL JOURNAL OF SCIENCE AND TECHNOLOGY, 2025)
This article explores the foundational concepts and principles of the anthropocentric paradigm in linguistics. By analyzing its development, philosophical underpinnings, and major linguistic directions, the study highlights the shift from object-centered to human-centered linguistic inquiry. The anthropocentric paradigm's influence is traced through cognitive linguistics, linguoculturology, and paremiology. The article also examines the implications of anthropocentrism for lexicography and phraseography. The findings demonstrate the paradigm's pivotal role in shaping contemporary linguistic methodologies and reinforce its enduring significance across diverse schools of thought.